Relational Graph Construction Method and Information Management System Based on the Relational Graph Convolutional Network. (3rd October 2022) - Dong, Yun; Zhang, Xixiang; Liang, Zhongfeng; Liu, Chao; Qin, Liming
Abstract : The Internet is like a huge neural network that is thought to be built, linking all the information in the human brain, and the communication between people is a part of the communication in the whole society. Social products are the medium of communication between people, so the efficiency of social products directly affects the efficiency of people and even the whole society. This paper mainly focuses on social applications as the object to carry out research. This paper is dedicated to optimizing the user experience and social experience of mobile social products, optimizing the design strategies of each process of social products, and exploring the possibility and development direction of social products in the future. Firstly, it conducts in-depth research on the related theories of human social behavior based on the social relationship graph and summarizes the factors that affect the intimacy between nodes in the social relationship graph. Then, it discusses the role of these factors in designing social products and studies how to apply these factors to all aspects of product development. Then, this design method using intimacy factor is abstracted and summarized into a design model, which is convenient for product developers to understand and use. Finally, the practice shows that the mobile social design method based on the social relationship graph can effectively guide the design of mobile social products and provide users with an intimate and efficient social experience that can meet the social needs of users. The accuracy rate is effectively improved by 21%, which proves the value and prospect of the research, design, and development of this topic in the field of mobile social products.